2021
DOI: 10.1088/1757-899x/1033/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Performance of PV integrated wall and roof as a building material

Abstract: The performance of the Photovoltaic (PV) module as a building material is analyzed by predicting the hourly variation in the room temperature compared to base case (conventional material). A computer simulation model of Fourier admittance method is used for the analysis. The average temperature fluctuation of PV roof and PV wall building compared to base case is 6.58°C and for PV wall 2.91°C respectively. The total daily energy generation from PV wall is found in the range of 6.7 kWh to 11.86 kWh, for PV roof … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The demand for and scale of the building, as well as the climate, heavily influence the integration of technology. [98] Under optimal operating circumstances, the PV modules utilized in the BIPV system generate energy at 13-20 % of incoming solar radiation. [99,100] The BIPV system temperature can rise to as much as 80 °C [55] in warm locations, [101] which impacts the system's performance.…”
Section: Design Options For Bipv Modulesmentioning
confidence: 99%
See 1 more Smart Citation
“…The demand for and scale of the building, as well as the climate, heavily influence the integration of technology. [98] Under optimal operating circumstances, the PV modules utilized in the BIPV system generate energy at 13-20 % of incoming solar radiation. [99,100] The BIPV system temperature can rise to as much as 80 °C [55] in warm locations, [101] which impacts the system's performance.…”
Section: Design Options For Bipv Modulesmentioning
confidence: 99%
“…Moreover, it may be categorized as a flat or pitched PV rooftop, PV double skin facade, PV glazing that is partially transparent, etc. The demand for and scale of the building, as well as the climate, heavily influence the integration of technology [98] . Under optimal operating circumstances, the PV modules utilized in the BIPV system generate energy at 13–20 % of incoming solar radiation [99,100] .…”
Section: Review Of Solar Cell and Bipv Technologymentioning
confidence: 99%
“…Singh et al analyzed the thermoelectric performance when using PV modules as building materials for walls and roofs. They found that PV walls and roofs have better thermoelectric benefits when combined with electric air conditioning devices with a high-performance coefficient [22]. Peng et al proposed a new type of C-Si-based PV window.…”
Section: Building Integrated Photovoltaicmentioning
confidence: 99%
“…Further, it can be classified as flat/pitched PV rooftop, PV-DSF, semi-transparent PV glazing, etc. The integration of technologies mainly depends upon the building demand, size, and climatic conditions [11]. The PV modules used in the BIPV system convert between 13-20% of incident solar radiation to electricity under ideal operational conditions [12,13].…”
Section: Overview Of Bipv Systemmentioning
confidence: 99%